Vasodilator oxyfedrine inhibits aldehyde metabolism and thereby sensitizes cancer cells to xCT‐targeted therapy. Issue 1 (22nd November 2019) - Otsuki, Yuji; Yamasaki, Juntaro; Suina, Kentaro; Okazaki, Shogo; Koike, Naoyoshi; Saya, Hideyuki; Nagano, Osamu
Abstract: The major cellular antioxidant glutathione (GSH) protects cancer cells from oxidative damage that can lead to the induction of ferroptosis, an iron‐dependent form of cell death triggered by the aberrant accumulation of lipid peroxides. Inhibitors of the cystine‐glutamate antiporter subunit xCT, which mediates the uptake of extracellular cystine and thereby promotes GSH synthesis, are thus potential anticancer agents. However, the efficacy of xCT‐targeted therapy has been found to be diminished by metabolic reprogramming that affects redox status in cancer cells. Identification of drugs for combination with xCT inhibitors that are able to overcome resistance to xCT‐targeted therapy might thus provide the basis for effective cancer treatment. We have now identified the vasodilator oxyfedrine (OXY) as a sensitizer of cancer cells to GSH‐depleting agents including the xCT inhibitor sulfasalazine (SSZ). Oxyfedrine contains a structural motif required for covalent inhibition of aldehyde dehydrogenase (ALDH) enzymes, and combined treatment with OXY and SSZ was found to induce accumulation of the cytotoxic aldehyde 4‐hydroxynonenal and cell death in SSZ‐resistant cancer cells both in vitro and in vivo. Microarray analysis of tumor xenograft tissue showed cyclooxygenase‐2 expression as a potential biomarker for the efficacy of such combination therapy. Furthermore, OXY‐mediated ALDH inhibition was found to sensitize cancer cells to GSH depletion induced by radiation therapy in vitro. Our findings thus establish a rationale for repurposing of OXY as a sensitizing drug for cancer treatment with agents that induce GSH depletion. Abstract : In the present study, we showed that the vasodilator oxyfedrine is a powerful sensitizer of cancer cells to xCT‐targeted therapy.